Value chain opportunities for women and young people in livestock production in Ethiopia: Lessons learned - Gebremedhin, Berhanu; Tesema, E.; Tegegne, Azage; Hoekstra, Dirk; Nicola, S. (International Livestock Research Institute, 2016)
Both young people and women contribute significantly to agricultural production in the African continent, although these contributions are not usually explicitly recognized in official statistics and documents. In Ethiopia, women traditionally have been subject to sociocultural and economic discrimination that resulted in fewer economic, educational and social opportunities than men. The traditional development approaches that view the household as a unitary decision-making entity and the assumption that interventions targeted at the household head would trickle down to household members is the foundation of the exclusion of women and young people. In particular, women in married households are usually excluded from development interventions. Many governments in Africa have now started to take policy measures to recognize and enhance the contributions of young people and women in economic growth on the continent. Similarly, there seems to be strong political commitment in Ethiopia to ensure inclusive economic growth that will result in better gender equality and benefit young people. This working paper summarizes the lessons from the experiences of the Improving productivity and market success for Ethiopian smallholders and Livestock and irrigation value chains for Ethiopian smallholders projects in inclusive value chain development aimed at benefiting women and young people. It mainly focuses on the trajectories of the two projects in reaching out to women and young people in order to increase their access to resources, innovation, technologies and knowledge which could consequently improve their inclusion in and benefits from value chain development and governance. Experiences from innovative extension methods for inclusion are discussed. The paper makes recommendations for policy and development practice to improve benefits to women and young people from development interventions.